A fluorescence active gold nanorod–quantum dot core–satellite nanostructure for sub-attomolar tumor marker biosensing. Issue 118 (17th November 2015) - Wu, Xiaoling; Gao, Fengli; Xu, Liguang; Kuang, Hua; Wang, Libing; Xu, Chuanlai
Abstract : The accurate monitoring of trace cancer biomarkers is crucial for the early diagnosis of cancer. Abstract : The accurate monitoring of trace cancer biomarkers is crucial for the early diagnosis of cancer. In the present study, we constructed a gold nanorod–quantum dot core–satellite assembly using a PSA-aptamer and its complementary DNA and developed an ultrasensitive fluorescence-aptasensor for the detection of prostate specific antigen (PSA) by monitoring fluorescence intensity. The limit of detection (LOD) for PSA was 0.029 aM, with an excellent linear range from 0.1 aM to 10 aM. This super-sensitive aptasensor was demonstrated to be robust in the analysis of human serum samples, and shows great potential for early cancer diagnosis and therapy.